Kontribusi Pertanian Berkelanjutan di Lahan Suboptimal Terhadap Aspek Lingkungan dan Sosial-ekonomi di Kecamatan Pulau Burung, Provinsi Riau - Ika Zahara Qurani; Sanudin Sanudin; Nurul Ihsan Fawzi (Jurnal Ilmu Pertanian Indonesia, 2022)
The circumstance of suboptimal land, due to its complex and often difficult nature, is either under-utilized and becomes abandoned space or over-utilized and generates environmental problems. In fact, suboptimal land, including peatlands, can be an alternative amid the decreasing area of arable land per capita for agriculture. This study aims to assess the contribution of sustainable agriculture for coconut commodities in the peatlands area, Pulau Burung District, Indragiri Hilir Regency, Riau Province. Data on environmental aspects were obtained from secondary data provided by the local company. Data on socio-economic aspects were obtained using focus group discussions (FGD) in five villages through semi-structured interview to 29 residents from various backgrounds. As a result, agricultural practices in this area can be deemed as sustainable based on water management indicators. The environmental impact is very minimal, biodiversity is preserved, and the subsidence rate is very low at 1.7 cm per year. In terms of socio-economic aspect, it can be concluded that the community perceives the environmental and social aspects are well maintained. Referring to the results of the FGD on agricultural practices, land fire control, food access, waste management, and water access are aspects that are considered adequate for the community. In contrast, land governance scored the lowest due to the difficulties in obtaining land certificates. Keywords: peatland, suboptimal land, sustainable agriculture, water management